Lugares de paso : puentes a la ciudad (2017)
"Places of passage: bridges to the city is a project framed in the city of Bogotá, Colombia. It's time is the year 2017, in which the construction of the metro transport system is anticipated, a project long time due, needed to fasten and relieve the saturated mobility system. The project seeks to become a transition between metro and other transport infrastructures with the urban tissue, broadening it's impact and creating places that encourage appropiation of the city, bringing back together enjoying and moving through urban space. Due to the anticipated progress in mobility, these places will be easily reachable to a great portion of the population, becoming a bridge to and from distant corners of the city."--Tomado del Formato de Documento de Grado.